Efektivitas Lagu Vowels untuk Meningkatkan Pengenalan Huruf pada Kelompok A TK Kemala Bhayangkari 31 - Shofia Fitri Yani; Basuki Hadi Prayogo; Trio Suwargono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This classroom action research evaluated the effectiveness of a simple vowel song (a, i, u, e, o) to enhance letter?recognition skills in Group A (ages 4–5) at TK Kemala Bhayangkari 31 Tanggul. Initial accuracy averaged 45%. The intervention was carried out executed over two Kemmis & McTaggart cycles (planning, action, observation, reflection), integrated the song with gestures into daily literacy routines. Data from structured observations, pre? and post?tests, and teacher reflections showed improvement to 70% in Cycle I and 90% in Cycle II. Video and field notes documented increased engagement, confidence, and autonomous use of song cues for identifying letter shapes and sounds. The findings suggest that short, repetitive musical activities with kinesthetic support effectively build early phonemic awareness and letter?shape association. This method is recommended for broader implementation in early childhood literacy programs and teacher training.